MORPHOLOGICAL VARIATION AND TAXONOMY OF LEPIDOCOLAPTES ANGUSTIROSTRIS (VIEILLOT, 1818) (PASSERIFORMES: DENDROCOLAPTIDAE) - BOLÍVAR-LEGUIZAMÓN, SERGIO; SILVEIRA, LUÍS FÁBIO (Papéis Avulsos de Zoologia, 2015)
Lepidocolaptes angustirostris is a South American woodcreeper that inhabits predominantly open lowlands such as the Cerrado, Chaco and Caatinga. Eight subspecies are currently recognized based on plumage patterns and geographical distribution. However, a more detailed morphological analysis and taxonomic revision have not been done in this species. The objective of this study was to conduct a taxonomic revision of L. angustirostris using morphometrical and plumage character, and a Generalized Linear Models analyzes (GLM) were elaborated to identify environmental variables that could account for this variation. We found a high level of intergradation among all named populations. The principal component analyzes show certain levels of morphological differentiation among the taxa, with a first component formed by bill characters (bill length, exposed and total culmen), and a second one that includes the bill width and the tarsus-metatarsus length. In the GLM analyzes, two climatic variables explain the geographical variation in the taxon, temperature seasonality and precipitation of warmest quarter. The ecogeographic rules of Bergmann and Gloger can be applied to this variation, and, more narrowly, the Allen's rule. Thus, the populations of the Narrow-billed Woodcreeper tend to be larger to the south of the distribution. We propose here that L. angustirostris is a single species, with no subordinate taxa. Any evidence analyzed here did not support the taxonomic validity of the proposed subspecies in the taxon. Despite colour-polymorphism identified in the plumage patterns, the high level of intergradation and the poor resolution of geographical boundaries did not support the splitting of this species.